Determinants of Sharia Investment Interest of The Bangka Belitung Community in The Digitalization Era - Efendi Sugianto; Rosida Dwi Ayuningtyas; Minarni (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2026)
This study aims to analyze the factors influencing public interest in Sharia investment in the Bangka Belitung Islands Province in the digital era. The research is motivated by the increasing development of digital-based Sharia economics and finance, which provides easy public access to various halal investment instruments. However, the level of public participation in Sharia investment remains relatively low compared to the region's potential. This study used a quantitative approach with descriptive and verification methods. Primary data were collected through the distribution of an online questionnaire to one hundred eighty respondents across seven regencies/cities in the Bangka Belitung Islands Province. The independent variables in this study included Sharia financial literacy, trust in Sharia financial institutions, religiosity, and ease of use of digital technology. The dependent variable was public interest in Sharia investment. Data analysis was performed using multiple linear regression with the assistance of SPSS version twenty six. The results showed that all independent variables had a positive and significant effect on public interest in Sharia investment. Ease of use of digital technology was the most dominant factor in increasing interest in Sharia investment, followed by trust in Sharia financial institutions, religiosity, and Sharia financial literacy. The coefficient of determination amounting seventy one point four percent indicates that the research model has a strong ability to explain the variable of Sharia investment interest. This study confirms that strengthening financial literacy, increasing public trust, strengthening religious values, and optimizing digital services are important strategies in supporting the development of inclusive, sustainable, and competitive Sharia investment in the Bangka Belitung Islands Province. Abstrak Penelitian ini bertujuan untuk menganalisis faktor-faktor yang memengaruhi minat masyarakat terhadap investasi syariah di Provinsi Kepulauan Bangka Belitung pada era digitalisasi. Penelitian dilatarbelakangi oleh meningkatnya perkembangan ekonomi dan keuangan syariah berbasis digital yang memberikan kemudahan akses masyarakat terhadap berbagai instrumen investasi halal, namun tingkat partisipasi masyarakat dalam investasi syariah masih relatif rendah dibandingkan potensi yang dimiliki daerah tersebut. Penelitian ini menggunakan pendekatan kuantitatif dengan metode deskriptif dan verifikatif. Data primer diperoleh melalui penyebaran kuesioner daring kepada seratus delapan puluh responden yang tersebar di tujuh kabupaten/kota di Provinsi Kepulauan Bangka Belitung. Variabel independen dalam penelitian ini meliputi literasi keuangan syariah, kepercayaan terhadap lembaga keuangan syariah, religiusitas, dan kemudahan teknologi digital, sedangkan variabel dependen adalah minat investasi syariah masyarakat. Analisis data dilakukan menggunakan regresi linier berganda dengan bantuan aplikasi SPSS versi dua puluh enam. Hasil penelitian menunjukkan bahwa seluruh variabel independen berpengaruh positif dan signifikan terhadap minat investasi syariah masyarakat. Kemudahan teknologi digital menjadi faktor yang paling dominan dalam meningkatkan minat investasi syariah, diikuti oleh kepercayaan terhadap lembaga keuangan syariah, religiusitas, dan literasi keuangan syariah. Nilai koefisien determinasi sebesar tujuh puluh satu koma empat persen menunjukkan bahwa model penelitian memiliki kemampuan yang kuat dalam menjelaskan variabel minat investasi syariah. Penelitian ini menegaskan bahwa penguatan literasi keuangan, peningkatan kepercayaan publik, penguatan nilai religius, dan optimalisasi layanan digital merupakan strategi penting dalam mendukung pengembangan investasi syariah yang inklusif, berkelanjutan, dan berdaya saing di Provinsi Kepulauan Bangka Belitung.